Effect of lupin flour incorporation on the physical characteristics of dough and biscuits - Jayasena, Vijay; Nasar-Abbas, Syed (Wiley-Blackwell Publishers, 2011)
Introduction: The incorporation of protein and dietary fibre rich lupin flour to biscuits has the potential to improve the nutritional value however it may adversely affect the physical and sensory properties. Objectives: To study the effect of lupin flour incorporation on the physical characteristics and sensory properties of biscuits to provide information to the potential manufacturers. Methods: Biscuit samples were prepared by substituting wheat flour with lupin flour at 0–50% levels. The samples were analysed for changes in dimensions, colour, texture and sensory properties.Results: Incorporation up to 40% level had no significant effect on biscuit diameter but thickness increased at ≥ 20%. No change in the L* values of dough and biscuits at ≤ 20% substitution. The a* values of dough decreased with increase in lupin flour concentration but in biscuit no significant change was observed up to 20% substitution. The b* values demonstrated a significant increase at ≤ 20% substitution. Biscuit hardness and fracturability demonstrated an increase with the increase in lupin flour concentration at ≥ 20%. Sensory evaluation revealed an improvement in colour with lupin flour substitution with no significant changes in taste, flavour, texture and overall acceptability up to 20% substitution. Conclusion: Lupin flour can be successfully incorporated into biscuits by replacing up to 20% of wheat flour to increase protein and dietary fibre contents.